Experimental studies on an extended end plate joint with prestressed bolts - Zwoliński, Tadeusz (Archives of Civil Engineering, 2026)
This paper presents the results of an experimental study of an extended end plate moment connection with prestressed bolts. Increments in bolt forces under loading were measured, as two solutions to eliminate those were compared. The first one consists of using a thick extended end plate to reduce prying action, the second one introduces a spacer plate to eliminate prying completely. Limiting increments in bolt forces is essential in the design of joints working under cyclic load, which can be prone to fatigue failure. Loss of preload was measured. Four types of connection setups were studied, two of which included a spacer plate installed between the extended end plate and a column flange. M16 grades 8.8 and 10.9 were used. The beam element was made of IPE 400 section, and the column element was made of HEB 220 section – both of S355-J2 grade steel. The possibility of using bolts not dedicated to prestress was explored. Finite Element Analysis using ANSYS Workbench software was performed. Results were summarised and discussed.